Collection and ethnobotanical investigation of Lentil (Lens culinaris Medik.) in Algeria - A. Abdelguerfi, D. Gaad, M. Laouar, (Recent Research in Science and Technology)
This study aims to make an inventory of the existing diversity and establish a representative collection of the diversity of lentil crop in Algeria. Surveys and collection of lentil accessions were conducted in different agro-ecological zones of Algeria In 2011. From ten regions (Departments), fifteen villages were surveyed and 30 lentil accessions were collected. The present study was carried out to survey, identify and document the uses of lentil accessions collected. The information on ethnobotanical uses was collected through semi-structured questionnaires with local villagers, elders and those people having knowledge associated with the production and utilization of lentil (Lens culinaris).The study revealed that among the interviewed farmers, 64% were males while 36% were females. The commonest cropping system found was the cultivation of lentil alone (95.5% of producers) and associated with grass pea (2.5%). Regarding the plant part used, two main parts are used by the farmers interviewed: seeds and the aerial part after harvest as a straw to feed animals. Low yield (40% of responses), disease and insect attack (36%), and low rainfall (24%) were the main production constraints reported by the interviewees.